Peran Kepuasan Pelanggan Pada Hubungan Kausalitas Antara Kualitas Layanan Terhadap Niat Beralih: (Studi Pada Pengunjung Hotel Fitra Majalengka) (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2021)
ABSTRACT This type of research is associative research. This research takes the title: “This type of research is associative research. This research takes the title: "The Role of Customer Satisfaction on the Causality Relationship Between Service Quality and Switch Intention (Study on Fitra Majalengka hotel visitors)”. The purpose of this study was to determine the partial effect of core service quality and encounter on switching intentions with the mediating factor of customer satisfaction. The population in this study were all visitors to the Fitra Majalengka hotel. The sampling technique used is purposive sampling. The number of respondents in this study was 120. The data were analyzed using structural equation modeling (SEM) with AMOS 21 software. The results of this study indicate that 1) core service quality has no effect on switching intentions, 2) encounter service quality has no effect on switching intentions, 3) core service quality has a positive effect on customer satisfaction, 4) encounter service quality has a positive effect on customer satisfaction, 5 ) customer satisfaction has a negative effect on switching intentions, 6) customer satisfaction mediates the negative effect of core service quality on switching intentions, 7) customer satisfaction mediates the negative effect of encounter service quality on switching intentions. An important finding from this study is that it can confirm the concept of EDT in which customer satisfaction becomes a mediating variable between the relationship between core service quality and encounter with switching intentions.